2018
DOI: 10.1007/s12576-018-0634-4
|View full text |Cite
|
Sign up to set email alerts
|

Matrine has pro-apoptotic effects on liver cancer by triggering mitochondrial fission and activating Mst1-JNK signalling pathways

Abstract: Mitochondrial homeostasis is closely associated with liver cancer progression via multiple mechanisms and is also a potential tumour-suppressive target in clinical practice. However, the role of mitochondrial fission in liver cancer cell viability has not been adequately investigated. Matrine, a type of alkaloid isolated from Sophora flavescens, has been widely used to treat various types of cancer. However, the molecular effect of matrine on mitochondrial homeostasis is unclear. Therefore, the aim of the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…In lung cancer, overexpression of Mst1 affects the feedback loop of p53 and JNK and ultimately exacerbates cancer cell death (Landry et al 2017). Moreover, Mst1 is a downstream effector of several anti-cancer drugs such as matrine (Cao et al 2018) and taurine. Recently, careful studies from several laboratories have further demonstrated that Mst1 regulates cell viability by targeting mitochondria (Zhou et al 2018c).…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, overexpression of Mst1 affects the feedback loop of p53 and JNK and ultimately exacerbates cancer cell death (Landry et al 2017). Moreover, Mst1 is a downstream effector of several anti-cancer drugs such as matrine (Cao et al 2018) and taurine. Recently, careful studies from several laboratories have further demonstrated that Mst1 regulates cell viability by targeting mitochondria (Zhou et al 2018c).…”
Section: Discussionmentioning
confidence: 99%
“…These data underscored the urgent need to develop more effective therapies against liver cancer. Recently, many potential new compounds have been demonstrated to possess anticancer cell abilities, including ailanthone [ 33 ], botulin [ 34 ], and matrine [ 35 ]. However, in vivo experiments were still needed for better illustration of their efficacies.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited attempts have been reported so far in clinical studies, implying a potential high risk and uncertainty of this anti-cancer strategy. Curiously, it has been recently reported that an excess of fission promotes mitochondrial dysfunction, which may play an unfavorable role in cancer cell growth 18 . Therefore, pharmacological induction of mitochondrial fission could provide novel insight into anti-cancer therapy, but this concept has not yet been adequately validated.…”
Section: Introductionmentioning
confidence: 99%